2007
DOI: 10.1177/0960327107076882
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial oxidative stress in female and male rat brain after ex vivo carbon monoxide treatment

Abstract: Carbon monoxide (CO) is the most common cause of fatal poisoning all over the world. At the cellular level, a combination of tissue hypoxia and direct cellular damage underlie the pathophysiology of CO toxicity. The purpose of this study was to determine the effect of CO treatment on oxidative stress parameters in mitochondria isolated from male and female rat brains. Mitochondria prepared from frontal cortex, hippocampus and corpus striatum were treated with 0.1% CO at 37°C for 30 minutes; control sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Expression of Nrxn1 was differentially regulated in the brain regions of OXT-exposed offspring regardless of the sex of the offspring; Nrxn1 was markedly downregulated in the amygdala but unchanged in the anterior cingulate and the somatosensory cortices of OXT versus control offspring. Because these results do not explain male-specific impairment of social behavior, we speculate that these changes could be due to sex differences in the response to oxidative stress (38,(50)(51)(52)(53)(54). The considerable sex difference in the expression of genes mediating oxidative stress 1 hour after OXT and the presence of persistently altered mitochondrial ETC proteins in the anterior cingulate cortex of only P28 male offspring support this viewpoint.…”
Section: Discussionmentioning
confidence: 90%
“…Expression of Nrxn1 was differentially regulated in the brain regions of OXT-exposed offspring regardless of the sex of the offspring; Nrxn1 was markedly downregulated in the amygdala but unchanged in the anterior cingulate and the somatosensory cortices of OXT versus control offspring. Because these results do not explain male-specific impairment of social behavior, we speculate that these changes could be due to sex differences in the response to oxidative stress (38,(50)(51)(52)(53)(54). The considerable sex difference in the expression of genes mediating oxidative stress 1 hour after OXT and the presence of persistently altered mitochondrial ETC proteins in the anterior cingulate cortex of only P28 male offspring support this viewpoint.…”
Section: Discussionmentioning
confidence: 90%
“…Unfortunately, as part of this work we did not expose cohorts to concentrations beyond 100 ppm CO to better define this relationship. However, previous work has demonstrated that exposure to 1000 ppm CO for 30 minutes inhibited CcOX within rodent forebrain mitochondria (44). Thus, by way of extrapolation, we postulate that CcOX activation lessens as the concentration of CO increases and that enzyme inhibition becomes a more prominent feature following exposure to concentrations greater than 100 ppm CO.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, because the experiments in the current study were carried out in animal models, the clinical implications of these results are yet to be examined using clinical studies. CO exposure is associated with memory impairment (Ryan, 1990; Bastin et al, 2004; Cutajar and Edwards, 2007; Wang et al, 2009), and elevated oxidative stress (Zhang and Piantadosi, 1992; Taskiran et al, 2007; Wang et al, 2009). CO concentrations in waterpipe smoke are substantial and a typical waterpipe use session involves inhalation of many cigarette equivalents of CO (Eissenberg and Shihadeh, 2009; Katurji et al, 2010).…”
Section: Discussionmentioning
confidence: 99%